Contractions Used in “Maleficent” Movie - Zainuddin Hasibuan (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2017)
The tiltle of this research  is “Contractions Used in Maleficent Movie”. “Maleficent” movie was directed by Robert Stromberg based on the originally story Disney's Sleeping Beauty La Belle au bois dormant by Charles Perrault. The background of this research, there are many contractions in “Maleficent” movie. This is good to learn and to use them (contractions) in daily life and maybe they are not found in other movies. The contraction spoken by movie players is sometimes very difficult to understand. The researcher choose this movie because this movie is so interest and inspire. The problem of this research is what contractions are used by the author in the movie “Maleficent” and how are contractions used by the author in the movie “Maleficent”. The purpose of this research is to find out contractions used by the author in the movie “Maleficent” and to explain contractions used by the author in the movie “Maleficent”. To achieve that purpose, the researcher conducted the qualitative research by library research. There are many contractions used by the author which can be classified into eight categories. The most dominant contraction is contracted pronoun. The second is verb contractions. The third are contracting not and ambiguous contraction. The fourth are negative contractions and contraction in tag question. The fifth are contracted noun and beware homophones.